KNOWLEDGE, PRACTICES, AND RELATED FACTORS REGARDING MEDICAL SOLID WASTE MANAGEMENT AMONG HEALTHCARE STAFF AT HAI DUONG MEDICAL CENTER IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current state of knowledge and practices regarding medical solid waste management among healthcare staff at Hai Duong Medical Center in 2025.Method: Cross-sectional descriptive study with analysis.Results: The results show that the percentage of staff with general knowledge of medical solid waste management is 76.0%. Of this, knowledge of medical solid waste classification is the highest (91.3%), followed by knowledge of collection at the lowest (58.0%); general practices in medical solid waste management are 90.7%. Multivariate analysis results show that: professional title and participation in training are related to knowledge attainment (statistically significant p
Keywords: Knowledge, practice of medical solid waste management, Hai Duong Medical Center.